Debate on "The benefits of a fixed Channel link" (Thomas Telford, 1985)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a debate held at Institution of Civil Engineers on 14 February 1985.